Developing a TikTok-Based Speaking Learning Model at Middle School to Strengthen Pancasila Student Profiles - Lisa Maurida; Jendriadi Jendriadi; Yanti Sariasih (AL-ISHLAH: Jurnal Pendidikan, 2024)
Education must continuously evolve to meet changing societal needs, with successful outcomes reflected in students' improvement in both knowledge and attitudes. Addressing low speaking skills among students at Takhfid Al Hidayat Middle School, this study develops a speaking learning model that leverages TikTok as an educational tool within Pancasila education, emphasizing democratic and moral values. This research employs a Research and Development (RD) methodology using the 4D model: Define, Design, Develop, and Disseminate. In the Define stage, we analyzed the development needs and user requirements. The Design stage involved drafting the initial media, while the Develop stage included expert validation to refine the media. Finally, the dissemination stage distributes the developed learning model. In a small-scale trial, the TikTok-based speaking model demonstrated improvement in students' speaking abilities, with an average pretest score of 55.73, increasing to a posttest average of 81.41. A broader trial reflected similar results, showing a pretest mean of 59.57 and a posttest mean of 71.71. These findings suggest that integrating TikTok into speaking activities significantly enhances students’ speaking skills. This model fosters engagement and supports the teaching of democratic and moral principles within Pancasila education. The developed TikTok-based speaking model effectively improves speaking skills and engages students in meaningful ways, making it a promising approach for language development and character education in Pancasila contexts.